The Nature of Binci-Binciki Kuli (Norma) of The Government of The Sultanate of Buton - Rizki Mustika Suhartono; Ermawati Ermawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted to determine the nature of Binci-binciki kuli (norms) in the Government of the Sultanate of Buton, this study used normative research that used library data or primary legal materials and secondary legal materials as well as tertiary legal materials. The results of this study indicate that the essence of Binci-binciki kuli (norms) of the government of the Sultanate of Buton contained in the Binci-binciki Kuli philosophy (pinch each other will feel pain) is formally listed in the Seven Dignity Constitution. It is recommended to preserve the value of the government of the Sultanate of Buton which are contained in the Binci-binciki Kuli philosophy (pinch each other will feel pain), which contains the principles of equality, equality and justice.